2013
DOI: 10.1128/jb.00997-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolic Systems Analysis of Pathogenic Burkholderia

Abstract: Burkholderia cenocepacia and Burkholderia multivorans are opportunistic drug-resistant pathogens that account for the majority of Burkholderia cepacia complex infections in cystic fibrosis patients and also infect other immunocompromised individuals. While they share similar genetic compositions, B. cenocepacia and B. multivorans exhibit important differences in pathogenesis. We have developed reconciled genome-scale metabolic network reconstructions of B. cenocepacia J2315 and B. multivorans ATCC 17616 in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 82 publications
4
57
0
Order By: Relevance
“…Some previous studies have compared Bp and Bt, their intracellular phenotypes and associated host inflammatory response [4, 7, 8, 10, 13]. Wand et al [28] observed an inverse association with their macrophage cytotoxicity and the virulence in mice after Bt infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have compared Bp and Bt, their intracellular phenotypes and associated host inflammatory response [4, 7, 8, 10, 13]. Wand et al [28] observed an inverse association with their macrophage cytotoxicity and the virulence in mice after Bt infected.…”
Section: Discussionmentioning
confidence: 99%
“…There are some similarities between Bp and Bt in terms of the ability of intracellular replication, cytokines induction, and immune cell differentiation [7, 8]. Bt has exhibited reduced replication in human macrophages and deficient invasion into epithelial cells compared to Bp [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Marked differences in the level of the pyridine nucleotides NADH and NAD + were observed between the first isolate retrieved from the patient and the late isolates IST4129 and IST4134. Since these cofactors are the most important redox carriers involved in metabolism, acting as electron acceptors in catabolic processes and providing the necessary reducing power for energy-producing redox reactions, having been proposed as involved in more than 120 reactions throughout B. cenocepacia metabolism (Fang et al, 2011; Bartell et al, 2014), it is tempting to speculate that the altered redox status of these isolates might contribute to several of the metabolite differences observed. Among the alternative pathways that can be used in the turnover of NAD + to NADH is the biosynthesis of glycine-betaine, L -tyrosine and L -leucine from betaine aldehyde, chorismate and valine, respectively (Bartell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The locus name of some of the genes and proteins with altered content in at least one of the late isolates compared with IST439 are also shown. This metabolic scheme was based on information gathered from KEGG PATHWAY Database (http://www.genome.jp/kegg/pathway.html), in BioCyc Database Collection (http://biocyc.org/) and in the metabolic reconstruction of B. cenocepacia J2315 (Bartell et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Rhamnolipids produced by P. aeruginosa have anti-staphylococcal activity [121] and act to decrease biofilm formation in order to maintain water channels [122]. B. cenocepacia J2315 has been shown to possess the operon required for rhamnolipid production [123], although the production of rhamnolipids has not yet been reported in this species. However, the porous biofilm phenotype shown in our study suggests the importance of water channels in B.…”
Section: Discussionmentioning
confidence: 99%